STUDENT THE LEGAL BASIS OF FORMING A WORLDVIEW AGAINST OPPRESSION AND AGGRESSION IN GIRLS - Uktamova Umida Sunatullaevna (Galaxy International Interdisciplinary Research Journal, 2022)
This article talks about increasing the activity of women in our country, opening wide doors of opportunities to female students, Violence - physical, mental, sexual or economic influence on women or girls or measures to influence them.